The Influence of Motivation, Business Capital and Marketing Strategy on MSMEs Development during the Covid-19 Pandemic in Takalar Regency - Agus Syam; Nur Armika Amir; Hajar Dewantara; Muhammad Jufri (Indonesian Journal of Business and Entrepreneurship Research, 2023)
The purpose of this study is to find out and analyze how the influence of motivation, business capital and marketing strategy on the development of MSMEs during the COVID-19 pandemic in Takalar Regency. This study uses quantitative methods with data collection instruments in this study, namely questionnaires, observations and documentation. Informants in this study were 71 SME in Takalar Regency. Based on the results of the study, the results of the partial test showed that the motivational variable had no and insignificant effect on the development of MSMEs during the COVID-19 pandemic in Takalar Regency, while business capital and marketing strategies had a significant and significant impact on the development of MSMEs during the COVID-19 pandemic in Takalar Regency. Based on the test results, motivation, business capital and marketing strategies simultaneously have a significant and significant impact on the development of MSMEs during the COVID-19 pandemic in Takalar Regency.